Initial phenological study of Campomanesia spp. of occurrence in the Cerrado, Goiás, Brazil - Pereira, Caio César de Oliveira; Vieira, Muza do Carmo; Leão, Érica Fernandes; Ferreira, Lara Bernardes da Silva; Lemos, Dalilla Cristina Socorro; Gomes, Júlia Graziela; Cubas, Erick Bryan; Vital, Nadielly Abadia Mendonça (Multi-Science Journal, 2017)
Não há.